ENDLESS JOURNEY OF THE HERO IN THE ‘CEMŞID U HURŞID’ OF - Ahmet DOĞAN (Fırat University, 2019)
In different platforms, though tale, story and mesnevi formed of a manifestation of the needing to tell of humankind apperantly presents